Repression and Monarchical Resilience in the Arab Gulf States. Issue 1 (2nd January 2017) - Lawson, Fred H.; Legrenzi, Matteo
Abstract: Why the uprisings that broke out across the Middle East and North Africa in 2010-11 ousted the leaders of republics but left monarchies largely intact remains puzzling. One promising explanation for the resilience of monarchical regimes argues that monarchs exercise repression in a comparatively restrained and largely effective fashion. Proponents of this theory tend to conflate two crucial causal factors: the level of state coercion exercised against opposition activists and the degree of indiscriminateness with which coercion is deployed. By treating these variables as analytically distinct, a more compelling explanation for monarchical resilience can be advanced. The advantages of the revised argument are illustrated by revisiting the divergent trajectories of the uprisings in Bahrain, Oman, Saudi Arabia and Kuwait.